PELATIHAN LSM PERPUSTAKAAN BJ SCHOOL BERBASIS WEB PADA YAYASAN BAITUL JIHAD BEKASI - Samsiana, Seta; Supratno, Setyo; Hasad, Andi; Marini, Sri; Sylviana, Rika; Rakhman, Taufiqur (LPPM Universitas Islam 45 Bekasi, 2021)
The progress of the library automation system (Library Management System) in the library has now been carried out, especially during a pandemic that requires maintaining distance and face-to-face contact. Starting from that thought, the UNISMA community service team is interested in holding library NGO (Library Management System) training activities Web-based BJ School. This BJ Scholl library website serves to present various information on books, journals and magazines, history and school vision and mission, member data, online book lending and book return data. Apart from the web, it also displays a link feature with several online libraries from several agencies. The training was carried out offline for 1 day and continued with online discussions. The training begins with the introduction of several topics about the website, followed by downloading and installation. Prior to the training, 100% of the participants had never created a website, either with wordpress or with other applications. And after the training, 60% of the participants have been able to apply website creation for their library. Some of the participants were constrained by a slow network and computer damage, so they were late in following the material given. All participants stated that this training was very useful.